FRI0387 Factors associated with osteoporosis and fracture in patients with sjÖgren primary syndrome. (12th June 2018) - Salman Monte, T.; Torrente-Segarra, V.; Sanchez-Piedra, C.; Fernández Castro, M.; Andreu, J.L.; Olivé, A.; Rosas, J.; Martínez Taboada, V.; ,
Abstract : Background: Primary Sjögren's syndrome (SSp) is a systemic autoimmune disease characterised by exocrine gland affectation and multisystem involvement. In addition to the systemic inflammatory affectation, patients with pSS have additional risk factors to develop osteoporosis (OP) and its major complication, osteoporotic fracture. Objectives: The aim of the study is to determine the sociodemographic and clinical factors of pSS associated with the presence of OP and osteoporotic fracture in patients with pSS from the SJOGRENSER registry. Methods: SJOGRENSER is a descriptive, cross-sectional and multicenter study of patients with pSS classified according to European-American consensus criteria. Patients attended in consultations of 33 Spanish rheumatology services were randomly included. Both the medical history and the medical interview were used to obtain the data. Epidemiological, clinical, serological and complications were collected. The continuous and categorical variables were analysed by means, medians and frequencies, with their respective deviations and interquartile ranges (p25-p75). Bivariate and multivariate analyses were carried out using a binomial logistic regression to study the factors associated with osteoporosis and osteoporotic fracture in pSS. Results: In the SJOGRENSER registry, 437 patients were included (95% women, with a median age of 58.63 (50.02–67.98) years). The prevalence of OP in the cohort was 18.54% (81 patientes). The prevalence of OP in men (n=21) was 19%, 2 men in the age group of 51–64 years and 2 in the group of >64 years. Three hundred of the women in the registry were menopausal (76.4%); a total of 67/300 women with menopausia had OP (15%). A total of 37 osteoporotic fractures (8.5%) were recorded in the cohort. Factors associated with OP in women with SSp in the bivariate analysis were: age (60.5% in the group of >64 years, 28% in the group of 51–64 years and 2.6% in the group ≤50 years, p<0.001), the time course of the disease (11.35 (SD 7.95) vs 7.8 (SD 6.14), p<0.001), the age of menopause (47(SD 7.29) vs 48.11 (SD 5.67), p=0.020), the ESSDAI (6 (DS 7) vs 4 (DS 5), p=0.020), and presence of anti-La (77.6% vs 64.7, p=0.030). In the multivariate analysis, there was an association between OP and age in the 51–64 age group, OR 9.993 (95% CI, 2.301–43.399, p=0.002), age >64 years, OR 20.610 (CI 95% 4.679–90.774, p<0.001) and time course of the disease, OR 1.046 (95% CI 1.008–1.085, p=0.017). Similarly, an association was found between the fracture and age in the 51–64 age group, OR 5.068 (95% CI, 1.117–22.995, p=0.035), age >64 years, OR 7.674 (95% CI 1.675–35.151, p<0.009), the time course of the disease, OR 1.049 (95% CI 1.003–1–097, p<0.036) and the ESSDAI score, OR 1.080 (95% CI, 1.029–1–134, p=0.002). Conclusions: Patients with pSS have a considerable prevalence of osteoporosis and osteoporotic fracture. Age and time of evolution were factors associated with the development of OP, and similarly, age, time of evolution of the disease and ESSDAI were factors associated with the development of fracture in patients with pSS. Disclosure of Interest: None declared